2019
DOI: 10.1007/s10490-019-09661-5
|View full text |Cite
|
Sign up to set email alerts
|

Indigenization of staffing in MNEs: The case of Saudi Arabia

Abstract: In the Gulf States, there has been increased emphasis on requiring MNEs to indigenize their staffing. Based on a survey of 157 HR directors in MNEs headquartered in Saudi Arabia, this article explores why so little headway has been made through applying and extending Resource Curse Theory. Surprisingly, we found formal ties with government had little effect; Resource Curse Theory would suggest this would be due to the concentration of regulatory scrutiny and support on the oil and gas industry, where, indeed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…It is held that, within emerging markets, organisations may depend on HR practices that are somewhat different from conceptualisations of HRM faced in mature markets (Webster and Wood, 2005). Therefore, the utilisation of ‘modern’ forms of HRM could have little or no impact on performance, given particular societal and economic realities (see Haak‐Saheem et al, 2017; Darwish et al, 2019; Wood et al, 2020; Singh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is held that, within emerging markets, organisations may depend on HR practices that are somewhat different from conceptualisations of HRM faced in mature markets (Webster and Wood, 2005). Therefore, the utilisation of ‘modern’ forms of HRM could have little or no impact on performance, given particular societal and economic realities (see Haak‐Saheem et al, 2017; Darwish et al, 2019; Wood et al, 2020; Singh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabi, MNEs have relied heavily on expatriates to manage their businesses and provide specialist skills and have invested little in recruiting and developing local talent (Wood et al, 2020). The effect has been to depress any incentive for locals to learn business skills, to develop technical knowledge or to seek jobs in the Saudi subsidiaries of MNEs.…”
Section: Governmental Localisation Policiesmentioning
confidence: 99%
“…In the Arabian Gulf region, the heavy reliance on expatriates has created an institutional environment in which local workers and job seekers are alienated, since employers have over time developed staffing and management systems and practices which perpetuate the continuing dependence on the foreign workforce (Al-Waqfi & Forstenlechner, 2014). The significant levels of government employment of Saudi nationals, with high salary levels relative to comparable rates in the private sector, contributes to an unwillingness amongst locals in Saudi Arabia to join MNEs (Wood et al, 2020). However, like other Gulf States, Saudi Arabia has spent heavily on automation in the government sector.…”
Section: Determinants Of Localisation Success: Impact Of Recruitmentmentioning
confidence: 99%
“…The same analogy that is applied to the age of the firm could be applied to the size of the firm. One possible explanation could be that firms -whether small or large -take the view that localization is an issue to be dealt with, but none accord any priority to it in order to add value to the success rate of localization (see Wood et al, 2019). Hence, it could be concluded that the size and age of the institution have no significant role when it comes to the success of localization policies for TNCs in Saudi Arabia.…”
Section: Firm Age and Sizementioning
confidence: 99%